Deadwood. The complete second season [videorecording (DVD)] - Milch, David, 1945- (HBO Video : Warner Home Video, 2006)
For better or worse, times are changing in Deadwood, and the transformation from camp to town is imminent. In an era of hard decisions and brutal power struggles among the camp's founders, they learn the hard way that fortune comes with a price.